(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The article provides a brief biographical sketch of Samuel Langhorne Clemens. The biographical sketch describes his upbringing and family experiences. In 1963, Clemens acquired the 'pseudonym' Mark Twain. A chronological list of Mark Twain's writings from 1867 to 1890. The author evaluated Mark Twain's notable writings, including The Chaliced Age and Tom Sawyer's Adventures, but only included one reference in his study. Maqolada Samuel Langhorne Klemensning qisqacha biografik eskizi keltirilgan. Biografik eskizda uning tarbiyasi va oilaviy tajribasi tasvirlangan. 1963 yilda Klemens Mark Tvenning "taxallusi" ni oldi. Muallif Mark Tvenning diqqatga sazovor asarlarini, jumladan, Tom Soyerning sarguzashtlarini baholagan, ammo o'z tadqiqotiga faqat bitta havolani kiritgan. В статье представлен краткий биографический очерк Сэмюэля Лэнгхорна Клеменса. Биографический очерк описывает его воспитание и семейный опыт. В 1963 году Клеменс приобрел «псевдоним» Марк Твен. Хронологический список произведений Марка Твена с 1867 по 1890 год. Автор оценил известные произведения Марка Твена, в том числе «Век чаши» и «Приключения Тома Сойера», но включил в свое исследование только одну ссылку.